2021
DOI: 10.1038/s41396-021-00920-2
|View full text |Cite
|
Sign up to set email alerts
|

Conserved and reproducible bacterial communities associate with extraradical hyphae of arbuscular mycorrhizal fungi

Abstract: Extraradical hyphae (ERH) of arbuscular mycorrhizal fungi (AMF) extend from plant roots into the soil environment and interact with soil microbial communities. Evidence of positive and negative interactions between AMF and soil bacteria point to functionally important ERH-associated communities. To characterize communities associated with ERH and test controls on their establishment and composition, we utilized an in-growth core system containing a live soil–sand mixture that allowed manual extraction of ERH f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
151
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(156 citation statements)
references
References 81 publications
3
151
1
1
Order By: Relevance
“…These exudates trigger a cascade of feedback loops among host plants, mycorrhizal fungi, and associated microbes around the hyphae (Jansa et al, 2013;Gorka et al, 2019;Jiang et al, 2021). In the case of arbuscular mycorrhizal fungi, hyphal exudates have pronounced effects on the growth and community of soil bacteria (Scheublin et al, 2010;Emmett et al, 2021) and induced positive interactions between arbuscular mycorrhizal fungi and specific bacteria contribute to soil nutrient transformation and turnover (including N and P) in the hyphosphere (Nuccio et al, 2013;Zhang et al, 2018). However, the mechanisms explaining how hyphal exudates recruit a functionally specific microflora, and to what extent host plants control these processes, remain poorly understood.…”
Section: Understanding Hyphal Exudate Profiles and Their Effectsmentioning
confidence: 99%
“…These exudates trigger a cascade of feedback loops among host plants, mycorrhizal fungi, and associated microbes around the hyphae (Jansa et al, 2013;Gorka et al, 2019;Jiang et al, 2021). In the case of arbuscular mycorrhizal fungi, hyphal exudates have pronounced effects on the growth and community of soil bacteria (Scheublin et al, 2010;Emmett et al, 2021) and induced positive interactions between arbuscular mycorrhizal fungi and specific bacteria contribute to soil nutrient transformation and turnover (including N and P) in the hyphosphere (Nuccio et al, 2013;Zhang et al, 2018). However, the mechanisms explaining how hyphal exudates recruit a functionally specific microflora, and to what extent host plants control these processes, remain poorly understood.…”
Section: Understanding Hyphal Exudate Profiles and Their Effectsmentioning
confidence: 99%
“…Inoculation with AM enhanced the water absorption in many of the plants that were subjected to drought stress. AM fungus mycelia can penetrate a larger volume of soil than the host plant roots, therefore increasing water absorption and transport to the roots and other plant parts, resulting in reduced drought stress [ 24 ]. Inoculation with the AM fungus significantly influenced morphological traits, increasing mostly leaf and tiller number per plant.…”
Section: Discussionmentioning
confidence: 99%
“…Rhizophagus irregularis), of which 12 showed phosphate-solubilizing activity (Sharma et al 2020). A distinct bacterial community closely associated with extraradical hyphae of Glomus versiforme, and conserved across divergent soils, was mainly represented by Proteobacteria (50% relative abundance), Actinobacteria (10%), Chloroflexi (9%), Acidobacteria (7%), Bacteroidetes (6%), and Fibrobacteres (4%) (Emmett et al 2021). An in vivo study reported, for the first time, that AMF hyphae may act as "transport agents" or "highways" for bacteria.…”
Section: Amycolatopsismentioning
confidence: 99%